Access to banking, savings and consumption smoothing in rural India - Vincent Somville; Lore Vandewalle (Graduate Institute of International and Development Studies, 2019)
Access to formal banking is increasing across the world and may transform how people manage their finances. We report from a field experiment that randomly provides access to a bank account to a representative sample of villagers in rural India. The treated respondents save actively into the account and their individual savings increase. There is, however, no signi cant impact on mean household savings nor on average expenditures, income, loans or transfers. Based on weekly data from financial diaries, we show the control households partially smooth consumption through transfers received from others. The treated households smooth consumption (and nutrition) better than the control households, thanks to pro-cyclical saving on the account. The latter result provides an important new insight into the role of banking in low and middle-income countries.
Keywords: C93; D14; G21; O16; O12; 330